SK Farm Livestock Management System - PUVAAN RAAJ; Mohd Zainuri Bin Saringat (Applied Information Technology And Computer Science, 2024)
A management system is designed to aid a business in managing its operations. SK FARM is a livestock farm that buys and sells livestock. The absence of a computer or web-based system is the owner’s major complaint since all administrative and business activities are completed by hand. To create, develop, and test a web-based livestock management system for SK Farm was the goal of this project. The system used computerized techniques and databases which is capable to arrange the owner’s financial information, orders, employee details and order placement for the customer. Information stored in databases provides security to safeguard the data while also making adding, updating, and removing operations much simpler. The PHP programming language was used to create it. The project adhered to the technique for software development using an incremental model. The system was hosted on the AWS web hosting service, and the database used the MySQL service.